Phosphorylation of Yellow Fever Virus NS5 alters methyltransferase activity - Bhattacharya, Dipankar (2008)
Serine/threonine phosphorylation of the nonstructural protein 5 (NS5) is conserved feature of flaviviruses, but the kinase(s) responsible and function(s) remain unknown. Mass spectrometry was used to characterize phosphorylated residues of yellow fever virus (YFV) NS5 expressed in mammalian cells. Multiple different phosphopeptides were detected. Mutational and additional mass spectrometry data implicated serine 56 (S56), a conserved residue near the active site in the NS5 methyltransferase domain, as one of the phosphorylation sites. Methyltransferase activity is required to form a methylated RNA cap structure and for translation of the YFV polyprotein. We show the 2’-O- methylation reaction requires the hydroxyl side chain of S56, and replacement with a negative charge inhibits enzymatic activity. Furthermore mutational alteration of S56, S56A or S56D, prevents amplification in a viral replicon system. Collectively our data suggest phosphorylation of NS5 S56 may act to shut down capping in the viral life cycle.